Determination of glufosinate-ammonium and malathion in residue oil from palm pressed fiber using high performance liquid chromatography - Muhammad Haziq, Russli (2012)
A study on the determination of organophosphorus pesticides (OPPs), namely glufosinate-ammonium and malathion in residue from palm pressed fiber (PPF). Three PPF samples were taken from three different areas, FELDA Lepar, FELDA Chini 1 and FELDA Chini 2.The extraction of oil residue in PPF was carried out using supercritical fluid extraction (SFE), using supercritical carbon dioxide (CO2) at 3000 psi in isothermal in 60°C for 60 minutes. Residue then were diluted uisng acetonitrile. Chromatogram of peak analyte was determine using Waters Alliance high performance liquid chromatography (HPLC) Dissolution System Series liquid chromatography interfaced to a 2998 Photodiode Array Detector. Determination was first done using standard malathion and glufosinate-ammonium of 10, 15 and 20 ppm run on a iscoratic elution mode for 30 minutes. Optimization method later was done using water and acetonitrile as mobile phase and run for 16 minutes for malathion and 20 minutes for glufosinate-ammonium. Malathion peak is retained at 8.0 minutes while glufosinate-ammonium at 16.0 minutes. Calibration curve of the standards were plot with R 2 values of 0.9085 for malathion and 0.9249 for glufosinate-ammonium. The detection limits (LOD) were 10.3 mg/L for malathion and 14.1 mg/L for glufosinate-ammonium. Later, determination of malathion and glufosinate-ammonium were done on real samples. For malathion determination, sample from Lepar showed to have concentraion of 19.46 ppm, Chini 1 (14.34 ppm) and Chini 2 (9.72 ppm). Determination of glufosinate-ammonium showed sample from Lepar to have concentraiton of 12.64 ppm, Chini 1 (17.72 ppm) and Chini 2 (39.64 ppm).